Estudo em pequenas parcelas sobre a fertilização do capim-gordura, Melinis minutiflora Pal de Beauv - Gomide, Jos´é Alberto (Revista Ceres, 2025)
A small-plot experiment was conducted in a massape soil type, 18% steep, with pH 5.1., in order to study the response of Molasses-grass (Melinis minutiflora, Pal de Beauv) to the three levels (0, 1 and 2) of: nitrogen, potash, phosphorus, sulfur and liming, respectively applied as: sodium nitrate orurea, common superphosphate, potassium chloride, gyppsum and lime.